"Dead honky"—against technologies of (white) violence. Issue 7 (9th August 2022) - Stewart, D-L
Abstract: In 1975, Saturday Night Live, a long-running sketch comedy television series, aired a sketch featuring Richard Pryor, a Black man, and Chevy Chase, a white man. During the sketch, several racial epithets were used for both Black people and white people, including the n-word. In this paper, I parallel the emotionalities displayed in that sketch to assert that as whiteness pretends to be innocent, flustered, and terrified, it nonetheless creates terror and violence. Critical whiteness studies (CWS) in the field of higher education fails to account for these technologies of violence that characterize whiteness and which whiteness employs. I bring a Black consciousness lens that asserts a critical narrative grounded in my own and in the intellectual, cultural, and psychic experiences of Blackness. From that space, I theorize technologies of (white) violence as enactments of: (1) malicious white terror; (2) rhetorical white innocence, mobilized through white contempt and white transmission; and, (3) pacifying white concession. Ultimately, I call for CWS to take up an analysis of technologies of (white) violence in its interrogation of the ways that whiteness operates in postsecondary education, but more so to commit to realizing the death of whiteness, taking up Pryor's verbal effigy "dead honky."